A New Lignan from Fruit of Schisandra wilsoniana A.C.Smith and its Anti-HIV activity - Fan, Yi-Ping; Duan, Li-Ping; Dong, Xiu-Hua; Dai, Yun; Li, Gan-Peng (Asian Journal of Chemistry, 2010)
A new lignan, willignan A, was isolated from the fruit of Schisandra wilsoniana A.C.Smith. It structures and stereochemistry was elucidated by analysis of spectroscopic data. This compound was evaluated for its inhibitory activity against HIV-1 and it shows an anti-HIV activity with EC50 (median effect concentration) value of 12.5 μg/mL and a Therapeutic Index (TI) above 16.00.